Teacher's pet eaudiobook - Clements, Andrew (Jake Drake, 2015)
Jake Drake doesn't try to become teacher's pet. It's just that all of his teachers- and even the principal-seem to think that everything he does is wonderful. They keep patting him on the head, but the kids in Jake's school are rolling their eyes whenever he walks by. Narrator Johnny Heller captures all the hilarious frustration of a kid who just can't seem to do anything wrong.